Genetic typing of classical swine fever viruses from Lao PDR by analysis of the 5' non-coding region. - Blacksell, S; Khounsy, S; Boyle, D; Gleeson, L; Westbury, H; Mackenzie, J (2005)
The 5' non-coding region (5'-NCR) of 27 classical swine fever virus (CSFV) isolates from Lao People's Democratic Republic (Lao PDR) during 1997 and 1999 were amplified by RT-PCR. A 150-bp region of the 5'-NCR amplicons was analysed and compared with reference CSFV of European and Asian origin and a phylogenetic dendrogram constructed. Following analysis, all viruses were determined to belong to genogroup 2. Viruses from Lao PDR grouped on a geographical basis with the majority of northern/central isolates falling into subgroup 2.1 and southern/central isolates falling into subgroup 2.2. These results concur with previous studies of CSF viruses from Lao PDR, although this study recognized the first occurrence of subgroup 2.1 in southern Lao PDR.